An Economics Analysis of Rice Production in Tripura, India - Hazari, S.; Chakraborty, N.; De, B. K. (Indian Journal of Hill Farming, 2018)
This study on production of rice in the all district of Tripura is based on the data collected from 160 rice producers from Khowai, Sepahijala, Unakoti, Dhalai, North, South, West and Gumati district during 2014-15. The costs on manures (21.72 %), hired male labour (14.90 %), have emerged as the major components in the total variable costs. The overall total cost on cultivation (Cost C3) of rice was found to be ₹ 42734.68 per ha and the overall return over Cost C3 was ₹ 42220.77 per ha. The results of the study revealed that rice cultivation in Tripura is a profitable enterprise as the returns per rupee invested have been found to be ₹ 1.99 on overall basis.